ALBERT DIETZ MESSIANISTIC MOVEMENT IN SEMARANG, 1918 - Ana Nurhasanah (Universitas Sultan Ageng Tirtayasa, 2015)
Albert Dietz's Messianistic Movement in Semarang is one of the social movements that occurred in the early twentieth century. Inside, it is very thick with religious elements and is led by a person with a higher education background who graduated from Europeesch Lagere School (ELS). The Messianistic movement led by Albert Dietz took place in Dukuh Kenang, the village of Bergaskidul Onderdistrik Lemahbang, Ungaran Afdeeling Salatiga District, Semarang. The background of the social, economic and cultural conditions of the majority of the people is an agrarian society. Difficult economic conditions and backwardness in education make people easily influenced to get involved in social movements. This also relates to the traditional mindset of society.Judging from the typology of his movement, Albert Dietz can be categorized as a movement leader who has considerable charisma in front of his followers. In this movement, he tends to choose to become a shaman by using methods related to supernatural powers and mystical science. As an ELS graduate, it is a contradiction that this cannot be separated from his spiritual life background. The informal education given by his mother pays close attention to traditional Javanese cultural life, which resulted in Albert Dietz being colored by the values contained in the Javanese tradition.